The cuckoo clock of doom - Stine, R. L. (New York : Scholastic, 1995)
When his father buys an antique cuckoo clock with a secret flaw, Michael accidentally reverses time while playing a trick on his little sister.
"A Parachute Press book"--T.p. verso.
"An Apple paperback.".
4.1.
4.1
5-8
Keywords: Clocks and watches -- Fiction; Horror stories; Time -- Fiction; Clocks and watches -- Fiction; Horror fiction; Time -- Fiction